Analisis Pengaruh Temperamen Individu Terhadap Tingkat Stres Kerja Pegawai Dinas Kelautan dan Perikanan Provinsi Sumatera Barat - Khalifahmi Amran (Jurnal Bisnis dan Manajemen, 2019)
The purpose of this study was to determine and analyze the effect of individual temperament on work stress levels. The populations in this study were employees of the ASN (Civil Servants) in the Department of Maritime Affairs and Fisheries of the Province of West Sumatra, which until December 2019 with total populations are 97 peoples. Samples were taken with a purposive sampling technique of 83 peoples. The results of this study found that: (1) Melancholic individual temperament has a significant effect on work stress levels. The higher one's individual temperament, the higher the work stress possessed by someone, (2) The magnitude of the effect of individual temperament on the level of work stress of ASN employees with a determination coefficient R2 of 0.152 or 15.20%, this value is still lower than the influence of other factors that is equal to 84.80 % which is not included in this study, and (3) The most dominant factor in influencing work stress is Melancholic so this factor is the main priority that need to be considered in conducting future recruitment in order to achieve the vision and mission of the Department of Maritime Affairs and Fisheries of West Sumatra Province.